Immune checkpoint blockade opens an avenue of cancer immunotherapy with a potent clinical efficacy. Issue 8 (2nd July 2015) - Adachi, Keishi; Tamada, Koji
<x xml:space="preserve">Abstract</x> Recent progress in tumor immunology has revealed that tumors generate immunologically restrained milieu during the process of their growth, which facilitates the escape of tumors from host immune systems. Immune checkpoint molecules, which transduce co‐inhibitory signals to immuno‐competent cells, are one of the most important components conferring the immunosuppressive capacity in the tumor microenvironment. Cytotoxic T‐lymphocyte‐associated protein 4 (CTLA‐4) and programmed cell death‐1 (PD‐1) are typical immune checkpoint molecules intimately involved in the suppression of anti‐tumor immunity. Antibodies against those molecules have been developed, such as ipilimumab (anti‐CTLA‐4 antibody), nivolumab and pembrolizumab (anti‐PD‐1 antibody), and have been approved by regulatory agencies and used in some countries. Treatment with these antibodies demonstrates previously unobserved clinical efficacies superior to the conventional therapies. In this review, we first discuss the escape mechanisms of cancer from host immune systems, and then focus on the recent advances in immune checkpoint blockade therapy and on the new findings of related immune reactions, aiming to provide a better understanding of the novel cancer immunotherapies.